2002
DOI: 10.1146/annurev.micro.56.012302.160854
|View full text |Cite
|
Sign up to set email alerts
|

Microsporidia: Biology and Evolution of Highly Reduced Intracellular Parasites

Abstract: Microsporidia are a large group of microbial eukaryotes composed exclusively of obligate intracellular parasites of other eukaryotes. Almost 150 years of microsporidian research has led to a basic understanding of many aspects of microsporidian biology, especially their unique and highly specialized mode of infection, where the parasite enters its host through a projectile tube that is expelled at high velocity. Molecular biology and genomic studies on microsporidia have also drawn attention to many other unus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
333
0
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 461 publications
(345 citation statements)
references
References 94 publications
4
333
0
8
Order By: Relevance
“…The relationship of Microsporidia and fungi, supported by a body of evidence (for review see Keeling & Fast, 2002), is consistently recovered. Alveolates (ciliates+ Plasmodium) and the heterokont Ochromonas form a clade with the heterokont falling within the alveolates.…”
Section: Maximum-likelihood (mentioning
confidence: 83%
“…The relationship of Microsporidia and fungi, supported by a body of evidence (for review see Keeling & Fast, 2002), is consistently recovered. Alveolates (ciliates+ Plasmodium) and the heterokont Ochromonas form a clade with the heterokont falling within the alveolates.…”
Section: Maximum-likelihood (mentioning
confidence: 83%
“…Younger queens are more susceptible to N. ceranae infection than older queens. This age response could be interpreted as the young queen gut cells promoting the growth, development, and germination of N. ceranae (Keeling and Fast 2002). Nevertheless, Rinderer and Elliot (1977) indicated that the protein conditions of the host are critical for the development of N. apis.…”
Section: Discussionmentioning
confidence: 99%
“…Initial phylogenetic analyses based on nSSU rDNA (Vossbrinck et al, 1987) and EF-1a (Kamaishi et al, 1996) provided support for the early divergence of Microsporidia in the eukaryotic phylogeny. However, results of these studies were challenged by subsequent molecular analyses using other protein sequences, such as aand b-tubulin, and RNA polymerase largest subunit (RPB1), which support the relatively late ancestry of Microsporidia, implying a phylogenetic affinity to the Fungi (reviewed in Keeling and Fast, 2002). Furthermore, recent analysis based on a-and b-tubulin indicates that Microsporidia originated from within the Zygomycota (Keeling, 2003).…”
Section: Did Microsporidia Evolve From Within the Fungi?mentioning
confidence: 99%